Roman stories ebook - Lahiri, Jhumpa (2023)
A BEST BOOK OF THE YEAR: THE NEW YORKER, NPR • The first short story collection by the Pulitzer Prize–winning author and master of the form since her number one New York Times best seller Unaccustomed Earth • Rome—metropolis and monument, suspended between past and future, multi-faceted and metaphysical—is the protagonist, not the setting, of these nine stories "A delectable, sun-washed treat . . . the stories have the beating heart of the city itself, a place of magnificent decay and vibrant, varied life." — Vogue In “The Boundary,” one family vacations in the Roman countryside, though we see their lives through the eyes of the caretaker’s daughter, who nurses a wound from her family’s immigrant past. In “P’s Parties,” a Roman couple, now empty nesters, finds comfort and community with foreigners at their friend’s yearly birthday gathering—until the husband crosses a line. And in “The Steps,” on a public staircase that connects two neighborhoods and the residents who climb up and down it, we see Italy’s capital in all of its social and cultural variegations, filled with the tensions of a changing city: visibility and invisibility, random acts of aggression, the challenge of straddling worlds and cultures, and the meaning of home. These are splendid, searching stories, written in Jhumpa Lahiri’s adopted language of Italian and seamlessly translated by the author and by Knopf editor Todd Portnowitz. Stories steeped in the moods of Italian master Alberto Moravia and guided, in the concluding tale, by the ineluctable ghost of Dante Alighieri, whose words lead the protagonist toward a new way of life.